BIOTECHNOLOGICAL ASPECTS OF SOUR BEER PRODUCTION - A. Khablenko; S. Danylenko; O. Dugan; V. Polishchuk; O. Yalovenko; D. Holubchyk (Harčova Nauka ì Tehnologìâ)
. The article presents a review of current biotechnological approaches to the production of sour beer styles, with a focus on the use of lactic acid bacteria (LAB) as a means of controlled acidification. Sour beer styles have gained wide popularity among consumers due to their vibrant flavor profiles, which are shaped by the activity of various groups of microorganisms. In particular, LAB play a key role in this process, as they are capable of producing lactic acid, thereby lowering the wort’s pH and ensuring the microbiological stability of the final product. The paper describes the features of different technological approaches to the production of sour beers: spontaneous fermentation (traditional lambics), mixed fermentation (American sour ales), kettle souring, primary souring, and less common methods such as sour mashing or pre-acidification of malt. Special attention is given to the advantages of the kettle souring method, which allows acidification prior to primary fermentation, ensuring consistent quality, reduced production time, and simplified process control. Based on literature analysis, it was established that among LAB, the most promising for use in brewing are representatives of facultatively and obligately heterofermentative LAB. The most extensively studied LAB species to date include Lactiplantibacillus plantarum, Lacticaseibacillus paracasei, and Levilactobacillus brevis, which are capable of growing in beer wort, rapidly lowering its pH, and contributing to the unique organoleptic profile of the beverage. At the same time, the article emphasizes the limited number of LAB strains suitable for use in sour beer production and highlights the need for further research aimed at the isolation, selection, and biochemical characterization of new technologically valuable cultures, as well as the optimization of their cultivation conditions.